Si-Miao-Yong-An Decoction for Diabetic Retinopathy: A Combined Network Pharmacological and In Vivo Approach - Du, Ao; Xie, Yumin; Ouyang, Hao; Lu, Bin; Jia, Wangya; Xu, Hong; Ji, Lili (Frontiers in Pharmacology, 2021)
Si-Miao-Yong-An decoction (SMYAD), a traditional Chinese medicine formula, is mainly used to clear away heat and detoxify and to promote blood circulation and relieve pain. Diabetic retinopathy (DR) is the most common type of microvascular complication caused by diabetes. This study is designed to examine the protective effect of SMYAD against DR and further to reveal the engaged mechanism via integrating network pharmacology and in vivo experimental evidence. Streptozotocin (STZ) was intraperitoneally injected into mice to induce diabetes. The dysfunction of the blood retina barrier (BRB) was observed by conducting Evan’s blue leakage assay, detecting tight junction (TJ) protein expression and counting the number of acellular capillaries in retinas. Our results showed that SMYAD alleviated BRB breakdown in vivo. Network pharmacology results demonstrated that regulating inflammation, immune responses, and angiogenesis might be associated with the efficacy of SMYAD in alleviating DR, in which the tumor necrosis factor (TNF) and hypoxia inducible factor 1 (HIF1) signal pathways were involved. Next, immunofluorescence staining results showed that SMYAD decreased microglia activation in retinas and reduced the enhanced adhesion of leukocytes into retinal vessels. SMYAD reduced the elevated serum TNFα content and retinal TNFα expression. SMYAD abrogated the activation of nuclear factor κB (NFκB) and HIF1α and consequently decreased the enhanced expression of some pro-inflammatory molecules and vascular endothelial growth factor (VEGF) in retinas. These results indicate that SMYAD attenuated DR development through suppressing retinal inflammation and angiogenesis via abrogating NFκB-TNFα and HIF1α-VEGF signal pathways.